Balloon closure of a surgical aorto-atrial communication. Issue 4 (October 1988) - Hayward, R; Kendall, B; Treasure, T
Abstract : Surgical repair of an extensive dissection of the proximal aorta (Shumway type A or DeBakey type I) was complicated by persistent haemorrhage from the surgical suture lines and via the false lumen. This was controlled by closing the aortic adventitia round the repaired aorta and by creating an anastomosis between the subadventitial space and the right atrial appendage. Though the haemorrhage was contained, the left to right (aorto-atrial) shunt led to a severe low output state, which was corrected by percutaneous closure of the fistula with a detachable balloon. A year after operation computed axial tomographic scanning showed the balloon in place though the para-aortic space persisted and communicated freely with the aorta.